how the quality of patents contributes to revitalising the innovation system?, evidence from the renewable energy sector (2021)
There is an intense discussion on the impact of the quality of patents on innovation and economic development. Consequently, measuring the quality of patents becomes an essential issue to understand how it affects the innovation system (IS). This paper shows a systematic review of patent quality indicators and their contribution to the literature. Additional to the systematic review, a dynamic behaviour hypothesis is developed to comprise how patent value indicators can be used to create a set of strategies to improve the innovation of the renewable energy sector. Our results show a novel framework for analysing the effects of patent value on the IS that could be useful for renewable energy diffusion in Latin-America.